2016
DOI: 10.1016/j.fcr.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability patterns among West African pearl millet landraces and prospects for pearl millet hybrid breeding

Abstract: a b s t r a c tPearl millet (Pennisetum glaucum (L.) R. Br.) is an important hybrid crop in India. However, to date limited pearl millet hybrid development has been undertaken in West Africa (WA), which is the center of pearl millet origin and diversity and where this crop is most important outside India. Using a diverse set of WA pearl millet germplasm, objectives of this study were to determine the superiority of population hybrids over open-pollinated varieties for agro-morphological and agronomic traits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 45 publications
7
51
3
Order By: Relevance
“…Several studies support a general superiority of pearl millet population hybrids derived from WA OPVs over established cultivars in the Sudano‐Sahelian target zone. Pucher et al (2016) reported a PMPH and PBPH for grain yield up to 73 and 69% with averages of 17 and 4%, respectively, when studying 20 WA pearl millet OPVs and their 100 offspring derived from a 10 × 10 factorial at six locations in WA in 1 yr. Ouendeba et al (1993) used a diallel mating scheme to evaluate combining ability of five improved Sahelian landraces at two locations over 2 yr in Niger. For grain yield, they found a PBPH up to 81% with an average of 44%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support a general superiority of pearl millet population hybrids derived from WA OPVs over established cultivars in the Sudano‐Sahelian target zone. Pucher et al (2016) reported a PMPH and PBPH for grain yield up to 73 and 69% with averages of 17 and 4%, respectively, when studying 20 WA pearl millet OPVs and their 100 offspring derived from a 10 × 10 factorial at six locations in WA in 1 yr. Ouendeba et al (1993) used a diallel mating scheme to evaluate combining ability of five improved Sahelian landraces at two locations over 2 yr in Niger. For grain yield, they found a PBPH up to 81% with an average of 44%.…”
Section: Discussionmentioning
confidence: 99%
“…It increased from 5.2 kg/ha/yr (1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964)(1965) to 24.0 kg/ha/yr (1996-2012) (Yadav and Rai, 2013). Genetic initial combining ability studies among WCA pearl millets were conducted in pearl millet, but without finding clear patterns (Pucher et al, 2016). However, promising hybrids developed from Nigerien and Senegalese varieties were found.…”
Section: Diversity Analysis and Implications For Heterotic Groupingmentioning
confidence: 99%
“…Although the average panmictic better-parent heterosis ranged from 4-18%, the best hybrids yielded up to 62% more than their superior parent. The importance of good parental per se performance to create high-yielding population hybrids was shown in all of these studies (Dutta, 2019;Ouendeba et al, 1993;Presterl & Weltzien, 2003;Pucher et al, 2016;Sattler et al, 2019).…”
Section: Pearl Millet Hybrids For West Africamentioning
confidence: 97%
“…Finding the appropriate hybrid type for WA is a major question in variety development. Heterosis effects are sufficiently large to develop profitable OPV‐derived population and topcross hybrids (Sattler et al., ), whereas the heterogeneity is expected to assure higher yield stability in contrast with homogeneous single‐cross hybrids (Bidinger et al., ; Mahalakshmi et al., ; Ouendeba et al., , 2005; Presterl & Weltzien, ; Pucher et al., ; Sattler et al., ). These studies support the conclusion that pearl millet topcross or population hybrid development are the most promising approach in WA for increasing yields without putting smallholder farmers at risk.…”
Section: Potential Of Pearl Millet Hybrids In Unpredictable West Afrimentioning
confidence: 99%
See 1 more Smart Citation